Three new arylbenzofurans from Lavandula angustifolia and their bioactivities. (March 2017) - Tang, Shiyun; Shi, Jianlian; Liu, Chunbo; Zhang, Fengmei; Xiang, Nengjun; Liu, Xin; Chen, Yongkuan; You, Junheng; Shen, Qinpeng; Miao, Mingming; Liu, Zhihua; Yang, Guangyu
Graphical abstract: Highlights: Three new arylbenzofurans were isolated from the whole plant of Lavandula angustifolia . The new arylbenzofurans showed higher anti-TMV activity than that of positive control. The arylbenzofurans showed weak inhibitory activities against some tested human tumor cell lines. Abstract: Three new arylbenzofurans, 2-(7-methoxy-2-(4-methoxyphenyl)-3-methylbenzofuran-5-yl)ethanol (1 ), 4-(5-(2-hydroxyethyl)-7-methoxy-3-methylbenzofuran-2-yl)phenol (2 ), and 2-(6-methoxy-2-(4- methoxyphenyl)-3-methylbenzofuran-5-yl)ethanol (3 ), together with three known ones (4 –6 ) were isolated from the whole plant of Lavandula angustifolia . Their structures were determined by means of HRESIMS and extensive 1D and 2D NMR spectroscopic studies. Compounds1 –3 and5 were tested for their anti-tobacoo mosaic virus (TMV) activities, and Compounds1 –6 were tested for their cytotoxicity activities. In our assay, Compounds1–3 showed high anti-TMV activity with inhibition rate of 38.2, 35.2, and 34.0%, which superior to positive control Ningnanmycin. Compounds1 –6 also showed weak inhibitory activities against some tested human tumor cell lines with IC50 values in the range of 2.2–8.2 μM.